TEACHING ENGLISH AT SMPIT ACEH BARAT: (A Descriptive Study of Teaching and Learning English) - Rina Syafitri Syukur; Puan Tursina; Endah Anisa Rahma (Getsempena English Education Journal, 2020)
The purposes of this study were to describe the ways of teaching English at SMPIT Aceh Barat in terms of pre activity, main activity and post activity, to discover the methods or techniques used by the English teachers at SMPIT Aceh Barat, and to seek the difficulties faced by the English teachers at SMPIT Aceh Barat. This study used qualitative method in nature. The research subjects of this study were two English teachers at SMPIT Aceh Barat who taught at seventh grade, eight grade and ninth grade. Observation and interview were used to collect the data. The data were analysed and interpreted through qualitative procedures. The results showed that the teachers who teach at SMPIT Aceh Barat have to be always creative and innovative and the school has to provide the good facilities in order to support the teaching and learning process becomes enjoy and fun.